2019
DOI: 10.1007/978-3-030-24305-0_40
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Textual Similarity Techniques in Code Level Traceability

Abstract: Automatic recovery of test-to-code traceability links is an important task in many areas of software engineering, like quality assurance and code maintenance. The research community has shown great interest in such a topic and has developed several techniques that already made significant advances in the field. These techniques include text-based learning algorithms, of which corpus is built from the source code of the software components. Several techniques based on information retrieval have been benchmarked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Thus, finding better performing textual methods can improve these possible combinations as well, having the potential of major contributions to the field. Our findings [4] show that improved versions of lexical analysis can significantly outshine the previously mentioned low results, raising their average precision over 50%.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Thus, finding better performing textual methods can improve these possible combinations as well, having the potential of major contributions to the field. Our findings [4] show that improved versions of lexical analysis can significantly outshine the previously mentioned low results, raising their average precision over 50%.…”
Section: Introductionsupporting
confidence: 48%
“…Thus, our results were evaluated on eight real opensource programs and also using a variety of source code representations and settings. Our previous work aimed to show that LSI itself performs better than it was previously perceived by the research community [5], investigated the question of source code representations in the task, and also found that Doc2Vec can significantly outperform LSI [6] while a suitable combination of the textual similarity techniques could provide even better results [4]. Some of the approaches used in the paper are also defined in our previous work but they are also briefly introduced in the following subsections.…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…For each program in the database, we obtained three different textual representations to measure similarity. We already described these representations in more detail in our previous works [24], [25]. Similar representations are widely used in other research experiments, such as [2], [26].…”
Section: B Code Representationsmentioning
confidence: 99%
“…Recommendation systems are not new to software engineering [39]- [41], presenting a prioritized list of most likely solutions seems to be a more resilient approach even in traceability research [24], [25], [42].…”
Section: B Classification Of Correct Patchesmentioning
confidence: 99%
See 1 more Smart Citation